The Influence of Firm Size, Debt to Equity Ratio, and Net Profit Margin on Income Smoothing in Food and Beverage Sector Manufacturing Companies Listed on the Indonesia Stock Exchange - Sari, Maya; Adenamora, Riska (International Journal of Economic, Technology and Social Sciences (Injects), 2023)
This research aims to determine whether there is an influence between Firm Size, Debt to Equity Ratio, and Net Profit Margin on Income Smoothing either partially or simultaneously in Food and Beverage Sector Manufacturing Companies listed on the Indonesia Stock Exchange during the 2018-2022 period. The approach used in this research is an associative approach, with a population of 27 companies and a sample of 20 companies taken using the purposive sampling method. The type of data used is quantitative data. Meanwhile, the data source is in the form of secondary data. The data collection technique used in this research is a documentation study technique that uses financial report data on the Indonesia Stock Exchange. The data analysis technique used in this research is logistic regression analysis. Meanwhile, data processing in this research used SPSS (Statistical Package for The Social Science) software for Windows version 22.00. This research proves that Net Profit Margin partially influences Income Smoothing. Firm Size affects Income Smoothing, and the Debt to Equity Ratio does not. It simultaneously states that Firm Size, Debt to Equity Ratio, and Net Profit Margin influence Income Smoothing in Manufacturing companies listed on the Indonesia Stock Exchange.